Strategi Utama Desa Adat Kutuh Kabupaten Badung untuk Meningkatkan Pariwisata sebagai Andalan Ekonomi - Damayanti, Devina Fadila; Rudyanty Winanda, Nieke (Jurnal Abdimas Pariwisata, 2025)
Kutuh Traditional Village is one of the villages in Badung Regency, Bali province. Kutuh Traditional Village has succeeded in changing its economic status from a poor village to a successful tourist village through various strategies. By utilizing village funds effectively, Kutuh Village developed nine tourism business units and three supporting service units, such as Village Credit Institutions and tourist attractions. Collaboration between traditional leaders and local governments also plays an important role in managing tourism, which now attracts around 3,000 tourists per day and generates annual revenues of up to 50 billion. This success is what makes Kutuh Traditional Village an example of other villages in Indonesia. This study employs qualitative research methods, gathering data through field lecture materials delivered directly by presenters serving as informants. For other supporting data, use journals, articles, books and others that are relevant to this research. This research shows that the Kutuh Traditional Village has implemented various strategies to increase tourism as an economic mainstay by utilizing village funds and has succeeded in developing nine tourism business units, including the Village Credit Institution (LPD).